The effect of ceramic shards waste material with the addition of variations of coconut fiber on compressive strength and UPV test in fiber concrete - Yolanda Oktovina Nurul Huda; Pintor Tua Simatupang (Jurnal Teknika, 2022)
Waste of coconut fiber (coco fiber) and ceramic shards has the potential that has not been maximally utilized. Using waste as a building material for concrete, can contribute to environmental sustainability and make buildings that are environmentally friendly (green building concepts) and economical. The study aimed to determine the effect of compressive strength and UPV test values produced by waste by ceramic shards of 25% as a substitute for coarse aggregate and coconut fiber as added concrete with variations of 0%, 0.50%, 1.0%, and 1.50% and good variations of concrete. The research method obtained from the results of testing of coarse aggregate, fine aggregate, cement, water, ceramic waste, and coconut fibers are used to determine the calculation of the concrete mix design, then make concrete samples. Based on the test results, the highest compressive strength at the age of 28 days was found in the 4th variation concrete (1.50% with 25% ceramic shard) of 32.95 MPa. From the results of the UPV test, the average velocity of the concrete was 3.5-4.5 m/s. From the results of the study, it was found that the result of the larger test was the UPV test because it looked at the density (velocity). Based on two test methods, the results obtained are increasing the compressive strength of concrete. Variations in the addition of coconut fiber and ceramic shard waste, it has an impact on the quality of the concrete that can achieve the quality of the concrete and the density between the aggregates binds to each other. Limbah serat sabut kelapa (coco fiber) dan pecahan keramik memiliki potensi yang belum maksimal digunakan. Dengan mempergunakan limbah sebagai material penyusun beton maka hal ini dapat berkontribusi terhadap kelestarian lingkungan dan menjadikan bangunan yang ramah lingkungan (green building concept) dan ekonomis. Penelitian bertujuan untuk mengetahui pengaruh nilai kuat tekan dan tes UPV yang dihasilkan limbah oleh pecahan keramik sebesar 25% sebagai substitusi agregat kasar dan serat sabut kelapa sebagai bahan tambah beton dengan variasi 0%, 0.50%, 1.0% serta 1.50% dan variasi beton yang baik. Metode penelitian yang diperoleh dari hasil pengujian agregat kasar, agregat halus, semen, air, limbah keramik, dan serat serabut kelapa digunakan untuk menentukan perhitungan mix design beton, kemudian dilakukan pembuatan sampel beton. Berdasarkan hasil pengujian hasil kuat tekan tertinggi pada umur 28 hari terdapat pada beton variasi ke-4 (1.50% dengan 25% pecahan keramik) sebesar 32.95 MPa. Dari hasil tes UPV didapatkan rata-rata hasil velocity beton 3.5-4.5 m/s. Dari Hasil penelitian didapatkan bahwa hasil pengujjian yang lebih besar yaitu tes UPV dikarenakan melihat dari kerapatan (velocity). Berdasarkan dua metode pengujian, didapatkan hasil meningkatkan kuat tekan beton. Dengan variasi penambahan serat serabut kelapa dan limbah pecahan keramik memberikan dampak kualitas mutu beton yang dapat mencapai mutu beton dan kerapatan antar agregatnya saling mengikat satu sama lain.